KOMPARASI KEEFEKTIFAN MODEL PEMBELAJARAN KOOPERATIF TIPE CRH DAN TAKE AND GIVE - Inayanti Fatwa (HISTOGRAM: Jurnal Pendidikan Matematika, 2021)
This type of research is an experimental unit research unit that aims to: find out the effectiveness comparison between the CRH type cooperative learning model and take and give type on cube and beam material in class VIII of State Junior High School 1 Takalar. The effectiveness of learning, in this case, is when the tests of mathematical learning outcomes, student responses, and student activities, all three have met the criteria of effectiveness. The population in this study was all students of class VIII of State Junior High School 1 Takalar and the sample consisted of two classes, namely the experiment class I was taught using a cooperative learning model type CRH and the experiment class II was taught using the Type Take and Give selected using simple cluster random sampling technique. The results showed that (1) THE CRH type cooperative learning model and take and give type were effectively applied to cube and beam materials, (2) THE CRH type cooperative learning model was more effective than the Take and Give type, (3) The learning and response results of math students of class VIII students who were taught with the CRH type cooperative learning model and take and give type have achieved minimal completion criteria,  (6) The minimum completion criteria of math and student response outcomes, taught with a CRH-type cooperative learning model are higher than the Take and Give type.